Plant fruits used as food by the Dayak community of Tamambaloh in Labian Ira’ang Village, Kapuas Hulu District, Indonesia - MARKUS IYUS SUPIANDI; LELIAVIA LELIAVIA; DIDIN SYAFRUDDIN; YUNIARTI ESSI UTAMI; RUFINA SEKUNDA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Supiandi MI, Leliavia, Syafruddin D, Utami YE, Sekunda R. 2019. Plant fruits used as food by the Dayak community of Tamambaloh in Labian Ira’ang Village, Kapuas Hulu District, Indonesia. Biodiversitas 20: 1827-1832. The Dayak Tamambaloh community has a long tradition of using plants as source of food. However, this knowledge of using the plants as food has not been scientifically documented. The objectives of this study were to identify the species of plants, especially fruit yielding plants, that which were used as food, and to document the methods of their processing practiced by Dayak Tamambaloh community. This study was conducted through the literature survey, interviews and field surveys in Labian Ira’ang Village, Kapuas Hulu District, Indonesia. The results of this study showed that Dayak Tamambaloh community in Labian Ira’ang Village use fruits of as many as 60 species of plants for edible purposes. They belonged to 29 plant families. The families with the highest percentage of fruit yielding plants were Moraceae (10%) and Cucurbitaceae (10%). The food plants were mainly obtained from forests (58.33%), gardens (16.67%), house yards (15%), river banks (5%) and hills (5%).